1992
DOI: 10.2527/1992.703818x
|View full text |Cite
|
Sign up to set email alerts
|

Apparent digestibility of amino acids in raw and heated conventional and low-trypsin-inhibitor soybeans for pigs

Abstract: An experiment was conducted with ileally cannulated pigs to determine the apparent digestibility of amino acids and N in raw or heated conventional or low-trypsin-inhibitor soybeans. Six littermate barrows initially averaging 24 kg were fed cornstarch-based diets (10.5% CP, .68% lysine, 3,558 kcal of ME/kg) supplemented with raw (unheated), conventional soybeans; raw, low-trypsin-inhibitor soybeans; heated, conventional soybeans; heated, low-trypsin-inhibitor soybeans; or solvent-extracted soybean meal. Heatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
3

Year Published

1993
1993
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 0 publications
3
47
0
3
Order By: Relevance
“…Third, thermal treatment is also known to improve protein digestibility by increasing the access of proteins to enzymatic attacks [7,28]. This is also consistent with the observation that the apparent digestibility of soyabean nitrogen in preruminant calves was negatively correlated with residual glycinin and p-conglycinin immunoreactivities which can be viewed as measures of protein denaturation [11].…”
Section: N Digestibility Feed Efficiency and Other Ratiossupporting
confidence: 75%
“…Third, thermal treatment is also known to improve protein digestibility by increasing the access of proteins to enzymatic attacks [7,28]. This is also consistent with the observation that the apparent digestibility of soyabean nitrogen in preruminant calves was negatively correlated with residual glycinin and p-conglycinin immunoreactivities which can be viewed as measures of protein denaturation [11].…”
Section: N Digestibility Feed Efficiency and Other Ratiossupporting
confidence: 75%
“…The duodenum was reported as the site where the stimulation of pancreatic enzyme secretion is regulated (Corring, 1974;Yen et al, 1977). The digestibility of crude protein and amino acids (Herkelman et al, 1992) was lowered by the trypsin inhibitors. A hyponutrient diet induced an increase in the length of all the intestinal sections not due to submucosal and serosal components, but the mucosa (Olkowski et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Herkelman et al (1992), studying the effect of the cultivars (with regular content x low content of KTI) and thermal treatment on the apparent digestibility of the protein of the soybean administered to swine, observed that the animals exposed to diets with conventional soybean presented lower performance, in comparison to the animals that received diets with soybean with low content of KTI. However, an adequate thermal treatment is required to improve the nutritional value of both types of soybean.…”
Section: In Vitro Digestibilitymentioning
confidence: 99%